The Ritual Music of Wana People - Giorgio Scalici (Graduate School of Institut Seni Indonesia Yogyakarta, 2014)
Very ancient practice, shamanism is usually found in the nomadic or semi- nomadic cultures. Given the dependence on the hunt for these populations, one of the fundamental roles of the shaman was to mediate between man and nature, especially between men and the lords of the animals that make possible the success of a hunting expedition. Shamanism has, however, shown a great ability to adapt to historical events, managing to keep up to us maintaining its uniqueness. Threatened by the arrival of progress and the world religions, has been able to respond actively and to influence the Western culture, as evidenced by the New Age movement and the presence of shamans in many movies, books and videogames. These fascinating, complex and archaic belief has always attracted the interest of the West, evidenced by historical, literary and academic publications, and it seems that still shamanism still has not exhausted what has to offer the world. In this article I am going to describe which the situation of the Wana religion to the present day is and which the rituals of this culture are. The Wana have two shamanic rituals - the momagu and the molawo ‒that face the disease with music, showing us the central role of music in the ritual life of this community, affirming - once again‒ the importance of music not just to Wana but also to humankind, and its relationship with the hidden world.